2022
DOI: 10.1093/narcan/zcac008
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic alterations at distal enhancers are linked to proliferation in human breast cancer

Abstract: Aberrant DNA methylation is an early event in breast carcinogenesis and plays a critical role in regulating gene expression. Here, we perform genome-wide expression-methylation Quantitative Trait Loci (emQTL) analysis through the integration of DNA methylation and gene expression to identify disease-driving pathways under epigenetic control. By grouping the emQTLs using biclustering we identify associations representing important biological processes associated with breast cancer pathogenesis including regulat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 70 publications
1
19
0
Order By: Relevance
“…The fact that the pre-selected CpGs were also strongly associated to expression levels of genes [17] enabled us to calculate a “translated” signature by multiplying the methylation beta coefficients with the correlation coefficients of the gene with highest absolute correlation, thus constructing a predictive signature that could be applied also on gene expression data ( Table 1 ). When applying this signature to the gene expression data ( Supplementary Figure1B ) we obtained an area under the ROC curves of 0.870.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The fact that the pre-selected CpGs were also strongly associated to expression levels of genes [17] enabled us to calculate a “translated” signature by multiplying the methylation beta coefficients with the correlation coefficients of the gene with highest absolute correlation, thus constructing a predictive signature that could be applied also on gene expression data ( Table 1 ). When applying this signature to the gene expression data ( Supplementary Figure1B ) we obtained an area under the ROC curves of 0.870.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that genome-wide associations ( in cis and in trans ) between DNA methylation and gene expression (emQTLs) are a powerful approach to identify transcriptional programs based on epigenetic modifications and TF activity, differentially regulated between patients [16, 37]. To identify such epigenetically regulated transcriptional programs involved in response to therapy as well as patient group-specific alterations in DNA methylation, we applied the emQTL approach to delta methylation and delta expression values before and after treatment with FEC +/- Bevacizumab (delta emQTL).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations